Evaluation of the infectivity and the persistence of Trichinella patagoniensis in muscle tissue of decomposing guinea pig (Cavia porcellus) - Fariña, Fernando Adrián (2017)
Trichinella patagoniensis, a new species of Trichinella, is widespread in Argentina. The success of parasite transmission depends, among other factors, on the resistance of L1 larvae present in the muscle tissue (ML) of dead hosts undergoing the decomposition process in different environmental conditions. The aim of the present work was to study the infectivity of T. patagoniensis muscle larvae in Cavia porcellus and the capability of the parasite to survive in decomposed muscle tissue of guinea pigs subjected to different environmental conditions. Thirty-two female Ssi:AL guinea pigs were orally inoculated with 2000 ML of T. patagoniensis (ISS2311). All the animals were sacrificed 42 days post-infection. Twenty-six animals were eviscerated, and carcasses were placed on the surface of soil inside plastic boxes that were exposed to environmental conditions in the summer 2014–2015 and autumn of 2015 in Buenos Aires, Argentina. Carcasses from six animals were placed into a plastic box inside the refrigerator at a temperature of 4 °C. The muscle tissue samples from the carcasses were examined weekly for the presence of larvae, and the infectivity of recovered ML was tested in BALB/c mice. Our results showed for the first time the ability of T. patagoniensis to complete its life cycle in guinea pigs, thus serving as a potential natural host. Also, larvae of T. patagoniensis remained infective in muscle tissue for several weeks while undergoing decomposition under different environmental conditions.